Attachment and attitudes toward children: effects of security priming in parents and non-parents. Issue 2 (4th March 2022) - Jones, Jason D.; Stern, Jessica A.; Fitter, Megan H.; Mikulincer, Mario; Shaver, Phillip R.; Cassidy, Jude
ABSTRACT: The present two-study investigation is the first to examine whether experimentally boosting attachment security (security priming) affects attitudes in the parenting domain for both parents and non-parents. Mothers (n = 72) and childless undergraduates (n = 82) were randomly assigned to a neutral or a secure prime condition and then completed measures of implicit attitudes (a child-focused version of the Go/No-Go Association Task) and explicit attitudes (self-reported) toward children. Following the priming manipulation, mothers in the secure prime condition had more positive implicit attitudes toward their child compared to mothers in the neutral prime condition. Security priming also increased mothers' positive explicit attitudes toward their children, but only among mothers who scored high on self-reported attachment-related avoidance. No priming effects emerged among non-parents. These results provide the first evidence for a causal link between parental attachment security and parental attitudes toward children.